RELATIONSHIP AMONG STUDENTS’ STUDY HABITS, ACHIEVEMENT, MOTIVATION AND ACADEMIC PERFORMANCE IN TERTIARY INSTITUTIONS IN KWARA STATE - Abdulkadir, Olarewaju Rasaq (Sokoto Educational Review, 2017)
The main purpose of this study was to determine the relationship among students study habits, achievement motivation and academic performance in tertiary institutions in Kwara State. The study was also to determine which of the variables is more related to academic petformance. Hence, correlation survey research design was used for the study. The sample for the study was made up of 384 students proportionately selected from the six tertiary institution used in Kwara State. The instruments used were questionnaires adopted from Bakare Study Habits Inventory, (1977) Bakare Need Achievement Scale (1977). Four hypotheses were postulated in the course of the study. The data were analysed and presented with the use of multiple repression and Pearson Product Moment Correlation ‘r’. The findings among others were that students of Kwara State tertiary institutions were effective in their study habits, high in the achievement motivation and academic performance, study habits and academic performance shows positive and significant relationship. However, the learning process in the course of proper guidance and counselling would lead the students to develop the ability to make decisions wisely and solve their problems independently., a deliberate policy should be put in place by both the state and federal government for the establishment of full fledge and guidance and counselling centres in tertiary institutions in the country. Achievement motivation and academic performance are significantly related, achievement motivation was more related to academic performance than study habit, there is also significant relationship between study habits and achievement motivation.